Molecular Response of Skin to Micromachining by Femtosecond Laser - Wang, Yutong; Wang, Shaoyang; Zhu, Yujie; Xu, Hui; He, Hao (Frontiers in Physics, 2021)
Pulsed lasers at the near infrared (NIR) range have been widely used in dermatology. Ultrashort pulsed picosecond lasers are found with the specific ability of very effective activation of skin repair and remodeling along with significant photodamage. Femtosecond lasers, with a shorter pulse width, may be a promising alternative to current NIR lasers in clinic. In this study, we performed optical micromachining by a femtosecond laser at 1,030 nm to skin of live mice in two modes of scanning of focused laser and direct irradiation by unfocused laser. The acute and one-day delayed immune molecular responses of the skin to the micromachining are studied by immunofluorescence microscopy of the skin sections. Our data shows the focused laser can activate remodeling of skin without any significant immune responses. In contrast, the direct irradiation by the unfocused laser activate significant immune responses in the deep dermis with high regulation of interleukin. Those results suggest focused femtosecond laser is of good promising potential in activation of skin remodeling and repairing with little immune or physical damage.